DESCRIPTION OF MATHEMATICAL PROBLEM-SOLVING ABILITY REVIEWED FROM THE LEARNING READINESS OF GRADE VII STUDENTS OF UNISMUH MAKASSAR MIDDLE SCHOOL - Sitti Rahmah Tahir; Rezki Ramdani; Sukmayanty Arifin (Almeera Education, 2025)
This study aims to: (1) describe the mathematical problem-solving ability in terms of the learning readiness of seventh-grade students of SMP Unismuh Makassar, (2) analyze how students with low, medium, and high learning readiness fulfill the four problem-solving indicators according to Polya (understanding the problem, making a plan, implementing the plan, and re-checking), and (3) identify the problem-solving stages that are most influenced by the level of learning readiness. This study uses a qualitative approach with a descriptive design. The data analysis technique uses the Miles and Huberman interactive model through three stages: data condensation, data presentation, and drawing conclusions. The results of the study show different patterns in problem-solving ability based on the level of learning readiness: (1) students in the low learning readiness category show limitations in three stages, only able to fulfill the indicator